Pointing model of new Pi of the Sky detector in Spain. - Cwiok, M.; Mankiewicz, L.; Opiela, R.; Siudek, M.; Sokolowski, Marcin; Zarnecki, A. (2011)
At the end of 2010 the new detector of the Pi of the Sky project was installed in the INTA El Arenosillo Observatory* near Huelva, Spain, at the coast of the Atlantic Ocean. The robotic telescope consisting of 4 CCD cameras on one parallactic mount was installed in the telescope dome of the BOOTES experiment from IAA. It can monitor about 0.5 steradians of the sky (40×40 degrees) with 10 s time resolution. The device is fully autonomous, designed to work without human supervision. After successful installation it had to be tested and optimally positioned before it started taking data. In this paper we describe in details deteremination of the Pointing Model for the new detector. © 2011 SPIE.